Interactions of β tubulin isotypes with glutathione in differentiated neuroblastoma cells subject to oxidative stress. Issue 7 (14th May 2018) - Guo, Jiayan; Kim, Hong Seok; Asmis, Reto; Ludueña, Richard F.
Abstract: Microtubules are a major component of the neuronal cytoskeleton. Tubulin, the subunit protein of microtubules, is an α/β heterodimer. Both α and β exist as families of isotypes, whose members are encoded by different genes and have different amino acid sequences. The βII and βIII isotypes are very prominent in the nervous system. Our previous work has suggested that βII may play a role in neuronal differentiation, but the role of βIII in neurons is not well understood. In the work reported here, we examined the roles of the different β‐tubulin isotypes in response to glutamate/glycine treatment, and found that both βII and βIII bind to glutathione in the presence of ROS, especially βIII. In contrast, βI did not bind to glutathione. Our results suggest that βII and βIII, but especially βIII, may play an important role in the response of neuronal cells to stress. In view of the high levels of βII and βIII expressed in the nervous system it is conceivable that these tubulin isotypes may use their sulfhydryl groups to scavenge ROS and protect neuronal cells against oxidative stress.